-1-5x=6-6x

Simple and best practice solution for -1-5x=6-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-5x=6-6x equation:



-1-5x=6-6x
We move all terms to the left:
-1-5x-(6-6x)=0
We add all the numbers together, and all the variables
-5x-(-6x+6)-1=0
We get rid of parentheses
-5x+6x-6-1=0
We add all the numbers together, and all the variables
x-7=0
We move all terms containing x to the left, all other terms to the right
x=7

See similar equations:

| 6x-8=5x+0 | | 1.5^x=1.23 | | 17=-8+9(a+5) | | 5-5x=11-4x | | -1(2x-4)=4.2x | | 22x-9+2x+16= | | f/4-15=15 | | 4x+6=-2(2x-5) | | -3y+48=4(y-2 | | 8z+7-5z=-24 | | 10y+8=4y+7 | | 12x-6=-4x-2 | | 18.26=3g+3.89 | | -16x–2=46 | | 7(5y-8)=29 | | 1−(2x+4)=−4x+5 | | 4(d-2)=4d | | -3(6d+8)=18+4d | | 16x-4=2x+14 | | 16-4=2x+14 | | -4x-37=-10x+53 | | -2v+9=3(-5v-6) | | 61=12x+8-2x | | h/3+9=27 | | 2(4x+5)=8x+10 | | w2+4w+12=228 | | 4000=p+(p)(0.09)(3) | | -34+6x=34+4x | | -3×+4=5x-7 | | -10=-4x–10 | | 9(1-5c)=-20 | | 2−2s=¾​s+13 |

Equations solver categories